The influence of job promotion, work motivation and preventive work discipline on employee performance in the regional secretariat Serang Regency - Dwi Meilinda Ayu Ningsih; Achmad Adi Ardiyanto; Ida Widiyawati; Haerofiatna Haerofiatna; Ali Imron (Institute of Accounting Research and Novation (IARN), 2026)
This study examines the influence of job promotion, work motivation, and preventive work discipline on employee performance at the Regional Secretariat of Serang Regency. The study used a quantitative method with a survey that included 98 civil servants as participants. Information was gathered through questionnaires and examined using multiple linear regression. The findings show that job promotions do not greatly influence employee performance, implying that promotion policies by themselves are not enough to boost performance unless they are backed by fair and transparent systems. On the other hand, work motivation is found to positively and significantly impact employee performance, highlighting the importance of internal drive, recognition, and encouragement in enhancing work outcomes. Preventive work discipline also shows a significant positive influence, reflecting the role of self-discipline, compliance with regulations, and responsibility in supporting optimal performance. Simultaneously, job promotion, work motivation, and preventive work discipline significantly affect employee performance, with the model explaining 49.8% of performance variance. These findings indicate that strengthening motivation and preventive discipline is more effective in improving employee performance than relying solely on structural promotion. The study contributes to human resource management practices in the public sector by emphasizing the importance of motivational and behavioral factors in enhancing organizational performance.